Lojas Marisa: moda e consumo popular - Garcia, Carolina Santos (2016)
This research aims to understand the following problem: how Marisa stores, which have dressed the working class since its creation, rebuilt itself, giving the brand a new meaning as a point of sale for fashion, while an addresser donor of competences, Marisa brings fashion for those who learn fashion as a value to be cultivated. The goal of this research is to analyze how being among global enterprises on Avenida Paulista, while being a local one, to present its new concept of retail chain and its consumers. The research structured a comparison amongst stores in a corpus composed by the two shops on Avenida Paulista, the store on Praça Ramos de Azevedo and the two stores on Largo Treze de Maio, as well as through the brand’s blog. The research was developed, firstly, by analyzing the elements that shape the visual identity and brand communication. Next, we set out to analyze the facades and insides of stores to understand how Marisa builds itself in different areas of São Paulo. Finally, we examined the windows of the store located between Avenida Paulista and Rua Peixoto Gomide, selected for better characterizing this new way of interaction and building brand visibility. To study the manifestations, the theoretical basis was the semiotics proposed by Algirdas Julien Greimas and the complementation of sociossemiótica of Eric Landowski. For the analysis of the plastic structure we turned to the work of Jean-Marie Floch and Ana Claudia de Oliveira and for the construction of ethos and pathos Marisa, we resorted to the studies of José Luiz Fiorin. We conclude that Marisa, by being installed at Avenida Paulista, it was set at a place of visibility that no other store of the network has, and this visibility is one of exquisite versatility that creates the aesthetic of dressing lower income groups. Thus, on the practical values platform ꟷ on which were once grounded the brand values ꟷ there is a symbolic investment, which is part of the Marisa’s construction as a brand that has the power to dress people in fashion and that is in fashion